Yeast nucleoporin mutants are defective in pre-tRNA splicing - Sharma, Kishore; Fabre, Emmanuelle; Tekotte, Hildegard; Hurt, Ed; Tollervey, David (Molecular and cellular biology, 1996)
We have screened nucleoporin mutants for the inhibition of tRNA splicing, which has previously been proposed to be coupled to transport. Strains mutant for Nup49p or Nup116p, or genetically depleted of Nup145p, strongly accumulated unspliced pre-tRNAs. Splicing was inhibited for all 10 families of intron-containing pre-tRNA, but no effects on 5′ or 3′ end processing were detected. Strains mutant for Nup133p or Nsp1p accumulated lower levels of several unspliced pre-tRNAs. In contrast, no accumulation of any pre-tRNA was observed in strains mutant for Nup1p, Nup85p, or Nup100p. Other RNA processing reactions tested, pre-rRNA processing, pre-mRNA splicing, and small nucleolar and small nuclear RNA synthesis, were not clearly affected for any nucleoporin mutant. These data provide evidence for a coupling between pre-tRNA splicing and nuclear-cytoplasmic transport. Mutation of NUP49, NUP116, or NUP145 has previously been shown to lead to nuclear poly(A)+ RNA accumulation, indicating that these nucleoporins play roles in the transport of more than one class of RNA.